Culture filtrate supplementation can be used to improve Mycobacterium tuberculosis culture positivity for spinal tuberculosis diagnosis - Beltran, Caroline G. G.; Venter, Rouxjeane; Mann, Theresa N.; Davis, Johan H.; Kana, Bavesh D.; Walzl, Gerhard (Frontiers in Cellular and Infection Microbiology, 2022)
Culture remains the gold standard to diagnose spinal tuberculosis (STB) despite the paucibacillary nature of the disease. Current methods can take up to 42 days to yield a result, delaying the ability to rapidly detect drug resistance. Studies have demonstrated the use of supplementation with culture filtrate (CF) from an axenic culture of Mycobacterium tuberculosis (Mtb) as a source of growth factors to improve culture rates. Our objective was to test a modified culture assay, utilizing CF supplemented media (CFSM), to improve culture positivity rates for suspected STB. Twelve patients with suspected STB were assessed by conventional culture (BACTEC™ MGIT 960), GeneXpert™ and standard histopathological examination. Spinal biopsies were taken from areas of diseased vertebral tissue or abscess, predetermined from MRI. Additional biopsies were obtained to assess CFSM for improved detection and faster culture of Mtb. All cases were diagnosed as STB and treated empirically for tuberculosis based on either bacteriological evidence (GeneXpert™, MGIT and/or CFSM positive), or based on clinical presentation. 5 specimens (45.45%) were positive for Mtb DNA as detected by GeneXpert™ and 1 specimen (8.33%) was cultured using MGIT (time to detection; 18 days). CFSM was able to culture 7 specimens (58.3%), with all CFSM positive specimens yielding a culture within 14 days. Two samples were positive only using the CFSM assay pointing to additional yield for diagnostic workup. Modification of standard culture can improve detection of Mtb and reduce time to positivity in individuals with STB where culture material is a requirement.